Neodymium and hafnium boundary contributions to seawater along the West Antarctic continental margin - Rickli, Jörg; Gutjahr, Marcus; Vance, Derek; Fischer-Gödde, Mario; Hillenbrand, Claus-Dieter; Kuhn, Gerhard (Earth and Planetary Science Letters, 2014)
Highlights: • Nd and Hf are released from sediments to the water column in the Amundsen Sea Embayment. • Seawater Nd and Hf isotope compositions show opposed trends close to the Marie Byrd Seamounts. • AABW is isotopically distinct in Nd between the Atlantic and the Pacific sectors. • Hf isotope variations occur between the sectors, but not with depth in each sector. Abstract: Neodymium and hafnium isotopes and elemental concentrations (Sm, Nd, Hf, Zr) have been measured in three water column profiles south of the Antarctic Circumpolar Current in, and to the east of the Ross Sea, in conjunction with five bottom water samples from the Amundsen Sea Embayment. Neodymium and hafnium both appear to be released from sediments in the Embayment. In the case of Nd, this is reflected in radiogenic isotope compositions (εNdεNd up to −5.4) and highly elevated concentrations (up to 41 pmol/kg). Hafnium isotopes, on the other hand, are only very slightly altered relative to the open ocean sites, and boundary release is most prominently indicated by elevated concentrations (>1 pmol/kg versus ∼0.7 pmol/kg). There is also a local input of both Hf and Nd at the Marie Byrd Seamounts, which leads to Nd isotope compositions as radiogenic as −3.1, and hafnium shifted to less radiogenic compositions in local bottom water. A compilation of the new data with literature data reveals a consistent view of the influence of Antarctica on the Nd isotope composition in Lower Circumpolar Deep Water (LCDW) and Antarctic Bottom Water (AABW). Sector specific Nd addition shifts AABW formed in the Atlantic sector to less radiogenic isotope compositions (average εNd=−9εNd=−9) relative to LCDW (average εNd=−8.4εNd=−8.4), whereas AABW in the Pacific sector is shifted to more radiogenic values (average εNd=−7εNd=−7). The evolution towards more radiogenic εNdεNd with depth in LCDW in the Pacific sector is likely to reflect admixture of AABW but, in addition, is also controlled by boundary exchange with the slope as observed at the Marie Byrd ...